Bio Micro-Nano Technologies of Antioxidants Optimised Their Pharmacological and Cellular Effects, ex vivo, in Pancreatic β-Cells - Mooranian A (Dove Medical Press, 2020)
Armin Mooranian,1 Nassim Zamani,1 Momir Mikov,2 Svetlana Goločorbin-Kon,3 Goran Stojanovic,4 Frank Arfuso,5 Bozica Kovacevic,1 Hani Al-Salami1 1Biotechnology and Drug Development Research Laboratory, School of Pharmacy and Biomedical Sciences, Curtin Health Innovation Research Institute (CHIRI), Curtin University, Perth, Western Australia, Australia; 2Department of Pharmacology, Toxicology and Clinical Pharmacology, Faculty of Medicine, University of Novi Sad, Novi Sad, Serbia; 3Department of Pharmacy, University of Novi Sad, Novi Sad, Serbia; 4Faculty of Technical Sciences, University of Novi Sad, Novi Sad, Serbia; 5Stem Cell and Cancer Biology Laboratory, School of Pharmacy and Biomedical Sciences, Curtin Health Innovation Research Institute, Curtin University, Perth, Western Australia, AustraliaCorrespondence: Hani Al-SalamiBiotechnology and Drug Development Research Laboratory, School of Pharmacy and Biomedical Sciences, Curtin Health Innovation Research Institute (CHIRI), Curtin University, Perth, WA, AustraliaTel + 61 8 9266 9816Fax + 61 8 9266 2769Email hani.al-salami@curtin.edu.auIntroduction: Recent formulation and microencapsulation studies of probucol (PB) using the polymer sodium alginate (SA) and bile acids have shown promising results but PB stability, and pharmacology profiles remain suboptimal. This study aimed to investigate novel polymers for the nano and micro encapsulation of PB, with the anti-inflammatory bile acid ursodeoxycholic acid (UDCA).Material and methods: Six formulations using three types of polymers were investigated with and without UDCA. The polymers were NM30D, RL30D, and RS30D and they were mixed with SA and PB at set ratios and microencapsulated using oscillating-voltage-mediated nozzle technology coupled with ionic gelation. The microcapsules were examined for physical and biological effects using pancreatic β-cells.Results and discussion: UDCA addition did not adversely affect the morphology and physical features of the microcapsules. Despite thermal stability remaining unchanged, bile acid incorporation did enhance the electrokinetic stability of the formulation system for NM30D and RL30D polymers. Mechanical stability remained similar in all groups. Enhanced uptake of PB from the microcapsule by pancreatic β-cells was only seen with NM30D-UDCA-intercalated microcapsules and this effect was sustained at both glucose levels of 5.5 and 35.5 mM.Conclusion: UDCA addition enhanced PB delivery and biological effects in a formulation-dependent manner.Keywords: probucol, microencapsulation, NM30D, ursodeoxycholic acid, diabetes, oxidative stress